2023
DOI: 10.55324/josr.v2i3.756
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Service Quality and Patient Satisfaction at the Neurology Polyclinic of Mohammad Natsir Hospital

Abstract: Quality health services are the needs and desires of every patient. Patient satisfaction is related to the quality of service they receive. This study analyzed the relationship between service quality and patient satisfaction at the neurology polyclinic of the Mohammad Natsir Solok Regional General Hospital (RSUD). Service quality according to Zeithaml et al has five dimensions, namely: Reliability, Assurance, Tangibles (physical evidence), Empathy (empathy), and Responsiveness knew as SERVQUAL. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Apart from that, the results of the research analysis also show that the waiting time for medicines is also due to the low compliance of DPJP in the use of e-prescriptions so that they still use manual prescriptions where in reality there are several prescriptions that are difficult for pharmacy staff to read which ultimately takes time to confirm back to the relevant DPJP. Susanty et al (2023) found that there is a relationship between the reliability dimension and patient satisfaction (p-value = 0.001). The reliability dimension is important because it relates to the accuracy of error-free services and patient satisfaction will decrease if the services provided do not match what was promised (Susanty et al, 2023;V, 2007).…”
Section: Results Figure 1 Patient Satisfaction Level Of Hospital Outp...mentioning
confidence: 96%
See 1 more Smart Citation
“…Apart from that, the results of the research analysis also show that the waiting time for medicines is also due to the low compliance of DPJP in the use of e-prescriptions so that they still use manual prescriptions where in reality there are several prescriptions that are difficult for pharmacy staff to read which ultimately takes time to confirm back to the relevant DPJP. Susanty et al (2023) found that there is a relationship between the reliability dimension and patient satisfaction (p-value = 0.001). The reliability dimension is important because it relates to the accuracy of error-free services and patient satisfaction will decrease if the services provided do not match what was promised (Susanty et al, 2023;V, 2007).…”
Section: Results Figure 1 Patient Satisfaction Level Of Hospital Outp...mentioning
confidence: 96%
“…Susanty et al (2023) found that there is a relationship between the reliability dimension and patient satisfaction (p-value = 0.001). The reliability dimension is important because it relates to the accuracy of error-free services and patient satisfaction will decrease if the services provided do not match what was promised (Susanty et al, 2023;V, 2007). Responsiveness is the ability of medical personnel to provide fast and accurate services to patients by responding to patient complaints and resolving complaints from patients and their families as well as conveying clear information regarding patient complaints (Setyawan et al, 2019).…”
Section: Results Figure 1 Patient Satisfaction Level Of Hospital Outp...mentioning
confidence: 96%
“…A suitable communication procedure between the patient and the doctor will favorably impact on both the patient's perception and the smooth running of the treatment. 19 The positive impact of the interaction between patients and dentists participating in RSGM UNPAD and orthodontists as consultant lecturers are also seen in the results of this study, where completely treated respondents are more sensitive to a midline deviation because they could assess a smile with the midline deviation starting at 2 mm as an unattractive smile on both the LCN and L photos, compared to untreated respondents group, where they could rate an unattractive smile starting at 3 mm deviation on the L photo and 4 mm on the LCN photos.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies regarding the perception of the midline deviation from the midline of the face, as perceived by the laypersons, still need to be revised. 12,15,[16][17][18][19][20] Research on the visual perception of the deviation in upper dental midline among orthodontic patients in Indonesia is still quite limited. However, the fact is that this information can be helpful for orthodontists when deciding how to treat complex cases of the midline deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Teori yang biasa digunakan untuk mengukur kepuasan pasien adalah teori Servqual yang mempertimbangkan kualitas pelayanan berdasarkan 5 dimensi yaitu bukti fisik (tangible), keandalan, daya tanggap, jaminan dan empati. Berdasarkan hasil artikel yang dikumpulkan dan dianalisis peneliti, diperoleh hasil bahwa terdapat hubungan antara kualitas pelayanan termasuk bukti fisik (tangible) dengan keandalan, daya tanggap, jaminan dan empati terhadap kepuasan pasien di fasilitas medis (Susanty et al, 2023). Teori kualitas layanan adalah pendekatan yang paling banyak diterima untuk mengukur kepuasan pasien, dengan mempertimbangkan lima dimensi: bukti fisik, keandalan, daya tanggap (bentuk layanan yang nyata), keamanan, dan empati (Kayame, 2023).…”
Section: Hasil Dan Pembahasan Hasilunclassified